2021
DOI: 10.3390/biomedicines9020112
|View full text |Cite
|
Sign up to set email alerts
|

Kisspeptin-8 Induces Anxiety-Like Behavior and Hypolocomotion by Activating the HPA Axis and Increasing GABA Release in the Nucleus Accumbens in Rats

Abstract: Kisspeptins (Kp) are RF-amide neuropeptide regulators of the reproductive axis that also influence anxiety, locomotion, and metabolism. We aimed to investigate the effects of intracerebroventricular Kp-8 (an N-terminally truncated octapeptide) treatment in Wistar rats. Elevated plus maze (EPM), computerized open field (OF), and marble burying (MB) tests were performed for the assessment of behavior. Serum LH and corticosterone levels were determined to assess kisspeptin1 receptor (Kiss1r) activation and hypoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 99 publications
2
24
0
Order By: Relevance
“…Concerning this, 6-MOF possesses an inherent GABA A agonist effect 23 and it has also been reported that an increased release of GABA in the nucleus accumbens results in hyperlocomotion that is mediated by inhibition of dopaminergic pathways in the ventral tegmental area and nucleus accumbens. 46 …”
Section: Discussionmentioning
confidence: 99%
“…Concerning this, 6-MOF possesses an inherent GABA A agonist effect 23 and it has also been reported that an increased release of GABA in the nucleus accumbens results in hyperlocomotion that is mediated by inhibition of dopaminergic pathways in the ventral tegmental area and nucleus accumbens. 46 …”
Section: Discussionmentioning
confidence: 99%
“…Several synthetic bioactive peptides related to urocortin 3, growth hormone-releasing hormone, neuromedin U, and kisspeptin, have antidepressant-like or anxiety-like effects via the receptors for neurotransmitters or the release of neurotransmitters [ 45 , 46 , 47 , 48 ]. The dysregulations of neurotransmitters, including GABA and glutamate cause mood disorders and Alzheimer’s disease [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Depression, anxiety and cognitive impairment are the most common symptoms of psychiatric disorders that may concur and/or sway during progression and comorbidity frequently occurs in mental illnesses, which renders the exact diagnosis even more difficult. Scrupulous studies are underway to untangle the thread of pathophysiology of mental disorders and their comorbidities not only in clinical medicine, but also in animal studies [106][107][108][109]. Psychological stress, especially depression has been found to be a risk factor for dementia, a prognostic biomarker for stokes and a therapeutic target for meaning-centered psychotherapy in depression, and animal-assisted and pet-robot interventions in dementia [110][111][112][113].…”
Section: Symptoms Inflammatory Status and Kynurenines In Psychiatric Disordersmentioning
confidence: 99%